Islamic aesthetics an introduction - Leaman, Oliver 1950- (The New Edinburgh Islamic surveys, 2004)
The reader is invited to view Islamic art as no more and no less than ordinary art, neither better nor worse than anything else that counts as art. It follows that there are no special techniques required in Islamic aesthetics as compared with any other form of aesthetics.